Análisis multitemporal de la tasa de deforestación mediante sistemas de información geográfica (SIG) en la Microcuenca Cañas. - Toala Bailón, José Antonio (2018)
The study is based on a multi-temporal analysis for the determination of the deforestation rate at the micro-watershed of the Cañas river by geographic information system (GIS). It has an area of 23.93 km2 that corresponds to a very small basin according to the classification of Campos (1998), with an undulating relief, cattle, agricultural and forestry soils, is subdivided into three areas Caña Grande, Caña Media and Caña Chica, the most representative tree species are the guasmo (Guazuma ulmifolia), guachapelí (Albizia guachapele) and samán (Samanea saman). Four satellite images of the national information system concerning the years 1990, 2000, 2008 and 2016 were obtained. The characteristics of these satellite images are WGS 1984 UTM Zone 17S, scale 1: 26,000. The supervised classification allowed the determination of three land uses in the Cañas micro-watershed for the different periods. 67.86% corresponds to agricultural areas, 26.36% arboreal vegetation and 5.78% to bodies of water in 2016. The application of the confusion matrix determined that the data obtained from land use occupation has 81, 25% confidence indicating an optimal value for the study. A deforestation rate of 4.19% of the micro basin was calculated in the last 20 years (1990 - 2016), resulting in a high rate of deforestation due to the change in land use, from forests to crops in the expansion of the agricultural frontier and livestock, where agricultural areas increased 1240.85 ha.